CULTURAL TRANSFORMATION THROUGH THE GAMBUSU’ IN BATTI’-BATTI’ PERFORMING ARTS OF THE SELAYAR ISLANDS: A RECONSTRUCTION OF LOCAL ARTISTIC TRADITIONS - Hatta, Harmin; Saputra, Andi Taslim (Boting Langi: Jurnal Seni Pertunjukan, 2025)
The gambusu’, a traditional musical instrument distinctive to the Selayar Islands, has undergone significant transformation in the practice of Batti’-Batti’ performing arts—both in its organological form and musical presentation—reflecting cultural shifts due to globalization. This study aims to analyze the cultural reprocessing of the gambusu’ in Batti’-Batti’ arts and examine the meaning of these changes as part of the local cultural reconstruction in Selayar society. Employing a qualitative-descriptive approach with a case study strategy, this research draws on participatory observation, in-depth interviews, documentation, and literature review, analyzed through Miles & Huberman’s interactive model. Findings reveal that the transformation of the gambusu’—now resembling an electric guitar—is not merely a physical alteration but also a representation of cultural adaptation to technology, the creative economy, and modern audience preferences. These changes further influence musical performance patterns, lyrical language use, and gender roles in performances. The evolution of the gambusu’ in Batti’-Batti’ arts reflects a strategic cultural reconstruction aimed at preserving traditional art forms. This study emphasizes the necessity of systematic documentation and the development of locally grounded arts education to ensure this cultural heritage remains vibrant and relevant for future generations.